Are Knee Biomechanics Different in Those With and Without Patellofemoral Osteoarthritis After Anterior Cruciate Ligament Reconstruction?. Issue 10 (October 2014) - Culvenor, Adam G.; Schache, Anthony G.; Vicenzino, Bill; Pandy, Marcus G.; Collins, Natalie J.; Cook, Jill L.; Crossley, Kay M.
<x xml:space="preserve">Abstract</x> Objective Patellofemoral (PF) osteoarthritis (OA) is prevalent following anterior cruciate ligament reconstruction (ACLR). This study aimed to investigate differences in transverse plane rotation between knees with varus and valgus alignment during gait in people with and without PFOA after ACLR. Methods Thirty‐six individuals who were mean ± SD 9 ± 2 years post‐ACLR (18 radiographic PFOA and 18 no knee OA) participated in this cross‐sectional study. Knee internal‐external rotation angles were measured using a 3‐dimensional motion analysis system during walking and running. Weight‐bearing frontal plane knee alignment, measured with an inclinometer, was used to classify participants as having varus or valgus alignment. Two‐way analysis of covariance was used to assess the effect of both PFOA and frontal plane knee alignment on dynamic knee internal‐external rotation. Results Significant interactions were found between PFOA status and frontal plane alignment on knee internal‐external rotation angles during walking (P = 0.019) and running (P = 0.002). Tests of simple effects revealed that during walking, individuals with valgus alignment and PFOA demonstrated a mean 3.9° (95% confidence interval [95% CI] 0.7, 7.1) less knee internal rotation than those with valgus alignment and no OA. During running this difference increased to 6.1° (95% CI 1.8, 10.4). For individuals with varus alignment, no significant effects were observed. Conclusion Less knee internal rotation during gait was found in individuals with PFOA and valgus alignment. A rotational shift of this magnitude may be sufficient to initiate or accelerate patellofemoral cartilage degeneration. Prospective studies are required to determine if these altered kinematic patterns result from, or contribute to, PFOA development after reconstruction.